Akuntabilitas dan Transparansi terhadap Kinerja Anggaran Berkonsep Value For Money: Komitmen Organisasi Sebagai Variabel Moderasi - Ni Putu Andini Saraswati; Dwi Suhartini (Universitas Batanghari Jambi, 2022)
The application of accountability and transparency ini budget performance with the concept of value for money in government organizations is important to study. The purpose of this study is to examine the effect of accountability, transparency on budget performance with the concept of value for money and organizational commitment as a moderating variable. This study uses a quantitative approach with the subject of anlysis are employees of the financial sector in BPKAD East Java, totaling 40 employees. The data analysis technique used WarpPLS 7.0. This study proves that the implementation of the value for money concept of budget performance is strongly supported by accountability and transparency. This illustrates that accountability and transparency can support better value for money concept budget perfmance.